(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Maintaining productive relationships in the workplace requires an emphasis on open and honestcommunication. Good professional relationships and mutual trust may be built via open and honestcommunication. How you handle organisational change is the single most important factor in its successor failure. Communicating with workers and making sure they are aware of the changes and how they willbe impacted is crucial. When it comes to implementing new technologies, most companies put theiremployees to work alongside management. Organizational change management is the focus of thisresearch, and its success depends on open lines of communication. The same is true of organisationschange is inevitable, just as it is in people’s lives. There is no way around the fact that any organisationwith aspirations of expansion, improvement, and fulfilment of its stated purpose will be immune to theconstant flux that is the result of the interplay between internal and external factors. It is important forbusinesses to adapt to their surroundings if they want to remain competitive and successful.